Psychobiology of dissociation and its clinical assessment - Ptacek, Radek; Bob, Petr; Paclt, Ivo; Pavlat, Josef; Jasova, Denisa; Zvolsky, Petr; Raboch, Jiri (Neuro endocrinology letters, 2007)
OBJECTIVE: Dissociation is often defined as partial or total disconnection between memories of the past, awareness of identity and of immediate sensations, and control of bodily movements, often resulting from traumatic experiences, intolerable problems, or disturbed relationships. This type of reaction to a psychological and/or physical trauma has often various neurobiological consequences and its clinical assessment has received enormous interest in recent psychological and neuroscience research. METHODS: Psychometric parameters of the Czech version of the Dissociative Experiences Scale were tested from the viewpoints of internal consistency, validity and factor structure, using data from a sample of n=783 adults, divided into three groups (epilepsy n=243, depression n=357, norm n=183), average age 39 years, SD=13.5. RESULTS: Findings of this study demonstrated that reliability, validity and factor structure of the Czech version of the Dissociative Experiences Scale correspond to those of the original English version. CONCLUSIONS: The Czech version of the questionnaire may be considered a suitable tool for estimating subjectively experienced dissociative symptoms.
Keywords: Epilepsy; Surveys and Questionnaires; epilepsie; Humans; lidé středního věku; psychologické testy; Female; Aged; dospělí; Psychiatric Status Rating Scales; senioři; lidé; reprodukovatelnost výsledků; Dissociative Disorders; průzkumy a dotazníky; Adult; ženské pohlaví; psychiatrické posuzovací škály; Male; Reproducibility of Results; Middle Aged; teoretické modely; Adolescent; Psychological Tests; Depression; disociační poruchy; Models, Theoretical; mužské pohlaví; deprese; mladiství